Characterization of red ginseng residue protein films incorporated with hibiscus extract - Kim, Hyeri; Yang, Hyun-Ju; Lee, Ka-Yeon; Beak, Song-Ee; Song, Kyung Bin (Food science and biotechnology, 2017)
An edible film was prepared from red ginseng residue protein (RGRP) and incorporated with hibiscus extract (HE). RGRP was extracted from red ginseng residue, which is an inexpensive by-product of the red ginseng processing industry. Different concentrations of HE were added to an RGRP film-forming solution as a natural antioxidant. The prepared RGRP films without HE had a tensile strength of 16.9 MPa and an elongation at break of 25.1%. The antioxidant activity of the RGRP film increased with increasing concentration of HE. In addition, the RGRP film with 1% HE exhibited the lowest value of water vapor permeability (1.88×10 −9 g·m/m 2 ·s·Pa), which indicates that the film has high water barrier property. The results present the production of edible films from discarded red ginseng residue, and the antioxidant activity of RGRP films as a packaging material can prevent lipid oxidation and quality loss of food products.